Effect of reinfusion of autologous blood on exercise performance in cross-country skiers - Berglund, B.; Hemmingson, P. (International Journal of Sports Medicine, 1987)
The effect of reinfusion of autologous blood (1350 ml) on exercise time over a specified distance (approx. 15 km) 4 weeks after phlebotomy ("blood doping") were investigated in six well-trained cross-country skiers. An additional control group of six well-trained skiers was included in the study. Test races were performed before phlebotomy, 3 h after, and 14 days after reinfusion of blood. In each test race, the mean time of the control group was set to 100% and the time of the blood-doped subjects expressed in percentage of the control group mean time. In the first control race, the mean time of the subjects who were later "blood doped" was 99.4% of the control group. However, both 3 h and 14 days after the reinfusion of autologous blood, the mean time of the blood-doped subjects was significantly lower (94.1%; P less than 0.05; 96.3%, P less than 0.05, respectively) than the control group. In conclusion, reinfusion of autologous blood stored in a refrigerator for 4 weeks after phlebotomy significantly increased performance expressed as race time in cross-country skiers. The significantly increased performance was observed both 3 h and 14 days after reinfusion.